Introducing the MMAD Repressive Actors Dataset - Espen Geelmuyden Rød; Jan Rustemeyer; Sabine Otto (Research & Politics, 2023)
We present the MMAD Repressive Actors Dataset (MMAD-RA). The MMAD-RA is a new data source that provides systematic information on the repressive actors present at protest events in autocracies, including their type, tactics, and level of violence. The data is temporally and geographically fine-grained, allowing for analysis between and within more than 60 countries from 2003 to 2012. The MMAD-RA enables analysis of the variation in repressive actors deployed to protests and their behavior, as well as how these actors impact protest dynamics and outcomes across political and socio-economic contexts. We believe the data will be a valuable resource for pushing forward research on how repressive actors engage with mass protests.